The The Influence Of Product Digital, Service Quality, and Price, On Purchasing Decisions Which Implicate Customer Satisfaction At BNI Life Insurance Jakarta - Septiowati, Rini (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Companies can introduce products so that efforts to fill the certainty of protection in the form of insurance for the community are met who have different needs from each other and become important besides the factor of seeking profit. This study is expected to be able to analyze how much Product, Service Quality, and Price Against Purchasing have Implications for Customer Satisfaction of PT BNI Life Insurance. This methodology is of the associative quantitative type. The sample uses 101 respondents. The analysis method uses linear regression analysis, the software used is SPSS 26. Research findings found that each variable, namely Product Digital, Service Quality, Price, Purchasing Decision and Customer Satisfaction, had a significant effect both partially and simultaneously. The multiple linear regression value Z = 1.502 + 0.354 X1 + 0.098 X2 + 0.378 X3 + 0.061 Y with an Fcount value of 51.860> Ftable 2.47 with a significance of 0.000 <0.05, from the regression equation obtained, it can be seen that price is an important factor with the highest value influencing BNI life insurance customer satisfaction, and the service quality factor must be improved because it also has an effect but the value is still small. .